Analiza porównawcza zagrożenia wodnego w wybranych kopalniach soli = Comparative analysis of water hazards in selected salt mines - Hudak, Magda; Szmaj, Łukasz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Mining industry is undoubtedly one of the most important industries. Without the possibility of mining and mineral processing technological developments would not be possible. Salt mines at the turn of the century had a great influence on the flowering of Polish state. An excellent example may be the royal county of Cracow, which generate significant revenue income of the former Polish state.
Keywords: zagrożenie wodne; kopalnie soli; threat to water; salt mines